2020
DOI: 10.1186/s12955-020-01419-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a short version of Lee Fatigue Scale used as a generic PROM in persons with stroke or osteoarthritis: assessment using a Rasch analysis approach

Abstract: Background: Fatigue is a common symptom associated with a wide range of diseases and needs to be more thoroughly studied. To minimise patient burden and to enhance response rates in research studies, patientreported outcome measures (PROM) need to be as short as possible, without sacrificing reliability and validity. It is also important to have a generic measure that can be used for comparisons across different patient populations. Thus, the aim of this secondary analysis was to evaluate the psychometric prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…high job search self-efficacy versus low job search self-efficacy). These psychometric properties provide useful information about the utility of a measure such as the JSSE (see Bragstad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…high job search self-efficacy versus low job search self-efficacy). These psychometric properties provide useful information about the utility of a measure such as the JSSE (see Bragstad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study suggested that trialists should consider using the entire library, especially for trials of experimental drugs to ensure they adequately capture potential adverse events 40 . Bragstad et al also highlighted that one challenge with using different short versions of a measure may be the difficulty of comparing the scores of the various versions with each other 41 . Finally, it was noted that while brevity should be a consideration, it should not outweigh the need to assess outcomes that participants consider important 23 .…”
Section: Measure Selectionmentioning
confidence: 99%
“… When selecting PROMs, the characteristics of candidate measures should be considered as these may contribute to potential respondent burden. Various issues as highlighted in the previous sections need to be carefully considered 4 , 22 24 , 27 30 , 32 – 34 , 37 , 41 45 . The delivery of PROMs may influence respondent burden.…”
Section: Key Considerations To Address Respondent Burdenmentioning
confidence: 99%
See 2 more Smart Citations